EARLY AND LATE OUTCOME AFTER REPAID AORTIC VALVE SURGERY - THE SINGEL CENTRE EXPERIANCE OF HEART CENTER LEIPZIG (GERMANY) - Sergey Leontyev; Nataliya V. Leonteva; Yaroslava Dmitrieva; Piroze Davierwala; Michael A. Borger (Креативная хирургия и онкология)
Introduction. The number of patients that need repeated operations on aortic valve due to dysfunction or degeneration of previously implanted prosthesis is constantly increasing throughout the world because of the constant growth of number of operated patients. The aim of our study was to assess the clinical outcomes of repeated surgeries for aortic valves, held at the Heart Centre of the University of Leipzig (Germany) from 1994 to 2008. Materials and methods. The study included 155 patients, 86 patients of which have had aortic valve prosthesis without reconstruction of the aortic root (rAVS) and 69 patients aortic root replacement (rAVR). The average time between operations amounted to 6.7 ± 7.9 years for all patients; 2.9 ± 3.1 and 8.8 ± 6.7 years for patients with implanted mechanical and biological valves, respectively. Results. The findings showed early lethality of 4.5% for all patients (3.5% for rAVS without root and 5.8% for rAVR with root, p = 0.5). Five-and eight-year survival is 66 ± 5% and 61 ± 6% for all patients and does not differ between surgical groups. Left ventricular ejection fraction is less than 30% (OR 9.2, 95% CI 1.1 -80.3) and initial neurological deficit (OR 22.1, 95% CI 2.3 -197.4) were independent predictors of early mortality. Independent predictors of late mortality were: NYHA functional class IV (HR, 95% CI 2.2 = 1.5, p -3.2 < 0.01) and infective endocarditis (HR 2.2, 95% CI = 1.4 -3.1 p < 0.01). Conclusions. Thus, repeated surgeries on aortic valve is associated with the acceptable early and late survival.